Urban skies safeguarded: innovative drone detection with programmable metasurface periscope - Hui Chu; Hanjun Zhao; Peng Li; Yong-Xin Guo (Nature Communications)
Abstract Programmable metasurfaces (PMSs) exhibit great potentials in target detection techniques, because they can take actions to change channel propagation characteristics which introduces further degrees of freedom for system optimizations. However, responses of most traditional PMSs are sensitive to incident angles of impinging electromagnetic waves, resulting in a failure of angular estimation to dynamic targets coming from different directions. Herein, by proposing a fully resonant structure and introducing a mode-alignment technology, we report an isotropic angle-insensitive PMS whose phase response is stable with respect to different incident angles in both elevation- and azimuth-planes. A radar scheme that uses such a PMS as a periscope is also demonstrated, to detect drones in a non-line-of-sight (N-LOS) scenario which usually happens in an urban environment. Our proposed scheme enables those targets even falling in shadow areas caused by high buildings to be successfully detected and tracked, which shows promising potentials in N-LOS target detections.